Analisis Kemampuan Memecahkan Masalah Matematika Siswa pada Materi FPB dan KPK di SDN Cikokol 3 Tangerang - Aam Amaliyah; Dini Damayanti; Siti Anisa Erika; Ummi Latifah (FONDATIA, 2022)
This study aims to determine the ability to solve mathematical problems of students on FPB and KPK materials in fourth grade students of SD NEGERI CIKOKOL 3. This research was conducted on fourth grade students in the odd semester of the 2021/2022 academic year. The research method used is exploration with random sampling techniques and classroom teacher interviews. The hypothesis is that students’ interest in learning mathematics in FPB and KPK is influenced by the result of learning basic multiplication and division as a sample. However, based on the data obtained from the result of random sampling and interviews, in this populations the result of learning mathematics in the FPB and KPK materials concluded that students’ mathematical problem solving abilities were still low. So that there are still some students who still do not understand the steps for solving problems because the teacher rarely asks problem solving questions. Students have difficulty solving FPB and KPK question because they cannot perform multiplication and division opertions which are prerequisite materials for FPB and KPK.